Biological reconstruction of the bone defects with free fibula flap after resections of extremity located bone tumors: Clinical and radiological short-term results - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Background: Recently, limb salvage surgery is a preferred method in orthopedic oncology and extremity-located bone tumors treated by limb salvage surgery have a 90%-95% success rate. The aim of the study is functional and radiological evaluations of the undergone biological reconstruction with free fibula flap (FFF) after tumor surgery and the effects of the defect size on the functional results. Subjects and Methods: Between 2005 and 2010, 13 patients (7M/6F) who underwent limb salvage surgery for benign/malignant bone tumors were included in study. Diagnoses included five osteosarcomas, six Ewing's sarcomas, one high-grade chondrosarcoma, and one aneurysmal bone cyst. Diaphyseal and metaphyseal regions of femur (7), humerus (3), tibia (2), and radius (1) were reconstructed. FFF was combined with a strut femoral allograft in seven cases. Postoperatively, partial weight-bearing allowed at postoperative 3 month and increased gradually. The mean follow-up was 25 months (12-60) and evaluated by extremity function scoring of Musculoskeletal Tumor Society (MSTS) and radiologically. Results: On the 6(th) month, in 92.3% of patients (12/13), evident union, and on the 12(th) month, in all of the patients, evident union and bone flap hypertrophy were observed. The mean MSTS score was measured 77.58% (46.66-100). As the resection size increased, the MSTS scores were significantly decreased (P = 0.027); as the bone flap size increased, there were relatively low MSTS scores (P = 0.440). On the patients without bone flap hypertrophy on 6(th) month, the bone flap size was measured relatively higher (P = 0.069) and the operation duration was relatively higher (P = 0.100). As the operation duration increased, there were relatively lower MSTS scores (P = 0.062). In cases where allograft and VFG combined (7/9 patients) had higher MSTS scores than the ones, only FFF was used (P = 0.621). Conclusions: Limb salvage surgery improves the life quality without worsening the prognosis and is a method that should be preferred. The biologic reconstruction of the defects with FFF, following extremity located musculoskeletal tumor resections have positive effects on functional outcomes.
Keywords: Biological reconstruction; limb salvage surgery; vascularized fibula; LIMB-SALVAGE TREATMENT; NONMETASTATIC OSTEOSARCOMA; ENDOPROSTHETIC REPLACEMENT; PROGNOSTIC-FACTORS; MALIGNANT-TUMORS; PROXIMAL TIBIA; DISTAL END; GRAFTS; ALLOGRAFTS; AMPUTATION